PELAKSANAAN DISIPLIN DAN MOTIVASI KERJA KARYAWAN PADA SMK PENERBANGAN BANJARBARU - Widarto Widarto; Feronika Lata Manjari (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
The purpose of this study is to determine the implementation of discipline and workmotivation of employees, to determine the factors that hinder the implementation ofdiscipline and work motivation of the employees of Vocational High SchoolBanjarbaru.The method used is descriptive. Data collection techniques are observations,interviews and documentation. Data analysis techniques use qualitative analysis.The results showed that the implementation of discipline and motivation was carriedout starting from discipline on working hours and teaching schedules, motivatingteachers and education personnel with incentives, conducting surveillance internallyand externally, implementing sanctions in the form of incentive cuts. For theimplementation of motivation, it is carried out by providing a salary according to theminimum wage, giving bonuses in the form of food allowance, overtime pay andother incentives, adequate work facilities, career paths, awards in the form of praise.The constraints faced in implementing discipline and motivation are the limitednumber of teachers and education personnel, the quality is not optimal, thecoordination of educators and education personnel needs to be improved and thework discipline is not maximal. Whereas alternative solutions to overcome theconstraint factor are increasing the number of permanent teachers throughappointment or through requests for assistance from Dpk PNS Teachers orcollaborating with other Public or Private Vocational Schools that have the samecurriculum, improving the quality of employees through Education and Trainingconducted by the Government and Programmed Education and Training. itself,building intensive communication through various media and creating or refining jobindicators to facilitate monitoring and evaluation.